Demiryollarında kullanılan hat kapasitesini belirleyen metodların incelenmesi ve Sirkeci-Halkalı kesimi için uygulamaları - Yavuzarslan, Eray (Fen Bilimleri Enstitüsü, 1999)
Demiryollarında kapasite, hat durumu, bakım-onanm hizmetleri, sinyalizasyon durumu, hat yapı ve üst yapının bütünleştiği bir kavramdır. Hat üzerinde işletilen trafiğin akışının uygun şekilde yapılması ve hatun taşıyabileceği tren sayısının bulunması ile birlikte kapasite artmmmın nasıl sağlanacağı günümüzde özellikle gelişmiş ülkeler için bir araştırma konusudur. Bu tez içersinde kapasite hesap yöntemlerinden UIC kodu ve bilinen klasik deterministik yöntemin bir kıyaslanması yapılmıştır. Mevcut hatlardan Sirkeci-Halkalı arası kapasite değerleri irdelenmiş ve hattın yeterli olup olmadığı araştırılmıştır. Bu bağlamda tez çalışması 6 bölümden oluşturulmuştur. Birinci bölümde, genel bir giriş yapılmış ve kapasite konusunda dünya demiryollarından ve ülkemizden örnekler verilmiştir. İkinci bölümde kapasitenin genel bir tanımı ile kapasiteyi etkileyen faktörler üzerinde durulmuştur. Aynca sinyalizasyon durumuna göre bloklara ayrılmış hat üzerinde minimum tren takip aralıklarının klasik olarak bulunmasından söz edilmiştir. Üçüncü bölümde, kapasite hesabı için esas alman Sirkeci-Halkalı arası banliyö hattı sinyalizasyon sistemi olan DRS ile Halkalıdan sonra Kapıkuleye kadar olan CTC sinyalizasyon sistemlerinin bir kıyaslaması yapılmıştır. Dördüncü bölüm içersinde, Uluslar arası demiryolları bMiğinin kapasite hesabı için sunduğu UIC kodu, bir örnekle sunulmuş ve Sirkeci - Halkalı banliyö hattına uygulanmıştır. xn Beşinci bölüm deterministik yöntemle kapasite hesabından bahsedilmiş ve Sirkeci- Halkalı banliyö hattının kapasitesi hesaplanmıştır. Altıncı bölüm genel bir değerlendirmenin yapıldığı bölümdür. Bu bölümde Halkalı- Sirkeci arası banliyö hattının kapasitesi çıkan sonuçlara göre yorumlanmış ve kapasitenin arttırılması için önerilerde bulunulmuştur.

This thesis presents a study on the subject of capacity. Capacity is such a subject that all world states give significant priority. So in this respect, a number of studies have been conducted by world railways on increasing capacity. The issues concerning increasing the number of trains operating on a single line and putting into operation the trains in the various categories on the same line have been significantly emphasized since the beginning of the century. Positive developments have been achieved on this issues thanks to the improvements in technology and extension of automation systems. The line capacities of the tracks are determined based on the following factors: - Structural factors:. Railway and signal plants. Operational factors:. Minimum train headway times,. Mixture of successive trains,. Direction checks in operating in both directions,. Frequency and gratitude of train headways in similar format,. Frequency and gratitude of stopping times,. Quality criteria demanded for operational running,. Period allocated for structural works in running schedule,. Non-operational period of the track in the night-time. XTV The factors above apply to all lines whether operating in a single direction or both directions. Within this thesis, the introductory part where the studies conducted by world railways on the issue of capacity are given, is followed by the part two where the principles of and factors influencing the capacity are evaluated. Furthermore, the latter part gives a calculation for duration of train headway times with classical methods. In the part three, CTC and DRS signaling systems that are most-widely used by Turkish railways, are compared. A DRS signaling system is available on the line between Sirkeci and Halkalı which was taken as basis for capacity calculation and the line between the Soğuksu Station which is just before Halkalı, and the border is operated with CTC system. These two systems are basically same but involve significant differences with respect to operation, which is the main theme of this part. DRS System is the one with button-switching, based on human control and a number of tools such as wireless, phone and telex are used to communicate within the control mechanism. Computer network is not extensive enough. It is one of the old systems of TCDD which involves an error margin based on the mood of engine- driver and arranger. CTC signaling system is completely based on a automation system. It is controlled by a central system. Its control table is quite modern with respect to that of DRS system. Human control is so little, if not, in signaling system. Therefore, the error risk is comparatively low. In addition to individual explanations concerning CTS and DRS systems, there is also a part for comparisons and proposals. In this part, a basic comparison between CTC and DRS systems is given and their respective effects on capacity are evaluated. UIC code which is taken as basis for capacity calculations by International Railways Association and its explanations are included in the part four. The world railways are able to obtain most accurate values from the capacity calculations with the help of this method which is more sensitive than any others. UIC code is based on modeling XV and takes into account the most inconvenient section of the line, not the entire line for capacity calculation, as with the classical deterministic method The most inconvenient section is in general chosen as the line between two successive stations, wherein the distance between the stations is the highest. The availability of an intermediate block post between the stations considered, is quite important with respect to continuity of the calculation. Average duration of minimum train headway time, taking into account the UIC code is K nij.tfij) tfa= [1] Snjj where A is the first station, B is the intermediate block post of the nature of interim station and C is the last station in the inconvenient section. And also i and j represent the previous and next trains respectively while n is the number of trains. In this case, the average duration of minimum train headway time is calculated based on the journey times of the both trains running on the line. The line capacity is calculated by L= [2] (tfa + tr+t^) taking into account the UIC code. Furthermore, the suburb railway track between Sirkeci and Halkalı which is one of the available lines of TCDD is examined as a sample and the track between Bakırköy and Yeşilköy on the same line is taken as the most inconvenient section according to UIC code. Yeşilyurt station is taken as the interim one. For the purpose of comparison, capacity calculations are made according to classical deterministic method in the part five. This method covers a system in which basic XVI formulas formerly used by world railways and currently used by TCDD to calculate the capacity, take part. This method is also based on modeling. The duration of minimum headway time of trains modeled thereby, is calculated for the entire line, the capacity of which is to be measured. It means that the inconvenient section is considered as the entire line. In this respect, the duration of minimum train headway time is taken into account with three different categories of headway: 1. Headway of the trains with the same journey times 2. Headway of the trains, wherein the faster train is the previous one 3. Headway of the trains, wherein the faster train is the next one. The minimum train headway time can also be calculated by graphical method. According to this method, stairs for stopping times are formed on the graphs of model trains taken over the running schedule. The minimum headway times are determined by intersecting the stairs for stopping times formed thereby with the highest block of the next successive train provided that the block of previous train will be on the top. The calculations made according to these cases, take part in the thesis. The capacity of line is L = _ _ [3] Z + Terf where T is the time period, z is the average duration of minimum headway time and rerf is the average stopping time. With the help of this formula, the capacity is calculated for a given period of time. On the Sirkeci-Halkah railway track, computations are made with the same method. The duration of niinimum headway time is determined with graphical method by forming and approximating stairs for stopping times for each train. xvn In the last part six, a general evaluation on the suburb track between Sirkeci and Halkalı which is taken as basis for the issue of capacity and calculations whereof, is given. The capacity values obtained by UIC code and deterministic method are compared and interpreted.
Investigation of the methods that determine the line capacity of raiunays and applications for Sirkeci-Halkalı line section
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1999
Keywords: Demir yolları; Hat kapasitesi; Kapasite arttırımı; Üst yap; İstanbul-Halkalı; İstanbul-Sirkeci; Railways; Line capacity; Capacity increase; Pavement; Istanbul-Halkalı; Istanbul-Sirkeci